Validation of the Brazilian versions of two inventories for measuring oral health-related quality of life of edentulous subjects - Souza, Raphael Freitas de; Silveira Dias Terada, Andrea Sayuri; Della Vecchia, Maria Paula; Regis, Romulo Rocha; Zanini, Ana Paula; Compagnoni, Marco Antonio [UNESP] (Wiley-Blackwell, 2012)
'Objectives: To analyse the validity of the Brazilian versions of OHIP-EDENT and GOHAI as assessment tools of edentulous subjects' OHRQoL.Background: Inventories for measuring oral health-related quality of life (OHRQoL) are important in clinical studies regarding oral rehabilitation. However, there is a need for comprehensive validation after translation into different cultural settings.Materials and methods: The sample comprised of 100 complete denture wearers (29 men, 71 women, mean age of 65.2 +/- 9.9 years). The associations between each OHRQoL inventory and other variables served as measurements of construct validity. Data analysis comprised the Spearman correlation test as well as multiple regression using the OHRQoL inventories as dependent variables and the other scales as determinants.Results: Both OHRQoL inventories showed good correlation with denture satisfaction, whereas lower correlation coefficients were found among the inventories and the HAD subscales. Denture satisfaction alone explained 48% and 39% of the variance found for the OHIP-EDENT and GOHAI, respectively, as assessed by multiple regression. A smaller effect was found for OHIP-EDENT.Conclusion: Both OHIP-EDENT and GOHAI showed good construct validity for measurement of OHRQoL of edentulous subjects.
Keywords: complete denture; edentulous mouth; patient satisfaction; quality of life; questionnaires